Potencialidades de uma sequência didática à luz da aprendizagem significativa para ensino da Primeira Lei de Mendel - Dias, Celina Pereira (2024)
The research in question arises from both a personal and professional need. The objective is to examine how educational processes face challenges, especially in the context of the curricular component in which the research teacher works - Natural Sciences. This is motivated by the profile of students, who enter education driven by the frequent and routine use of technological media. Therefore, it is the responsibility of the professional to plan pedagogical strategies that motivate students to actively participate in the learning process, with the aim of expanding their skills, as established by the National Common Curricular Base, especially for 9th grade students of elementary school, with regard to content related to Mendel's First Law, using methodologies that promote meaningful learning. The research seeks to answer the following question: what are the potential contributions of a didactic sequence structured in light of the Theory of Meaningful Learning to address content related to Mendel's First Law in Elementary School? The general objective was to develop, apply and evaluate a didactic sequence supported by the Theory of Meaningful Learning, to address the content of Mendel's First Law in Elementary School. The teaching sequence was applied to 13 students from a public school in Presidente Médici - RO, over 5 meetings totaling 10 hours. The methodology used was qualitative and the data collection instruments included pre- and post-intervention questionnaires, comic strips produced by the students and a logbook kept by the research teacher. The educational product linked to the dissertation is a teaching sequence intended for Elementary School Science teachers, addressing the introduction to genetics, cross-breeding and results obtained by Gregor Mendel, especially aimed at the 9th grade. The results of the data analysis indicated a positive reception of the activities based on the educational product by the students. They showed interest in having other classes using the applied methodology, highlighting the importance of ensuring the learning process through interaction and integration of the students in the proposed activities. The educational product, which makes up the teaching sequence on Mendel's First Law, is free and open access, in addition to being available for download on the PPGECM and EduCapes portal: http://educapes.capes.gov.br/handle/capes/742951.